Porous prussian blue nanocubes as photothermal ablation agents for efficient cancer therapy - Xue, Peng (2019)
Nanomaterial-based photothermal agents have attracted great attention as near-infrared laserdriven ablation agents for tumor therapy. In this work, Prussian blue nanocubes with porous interior were synthesized via controlled chemical etching method and successfully applied for efficient photothermal ablation of tumor cells in vitro. Monodispersed porous Prussian blue nanocubes (115.4±4.7 nm) were produced through a controlled self-etching reaction in the presence of polyvinylpyrrolidone (PVP). Owing to the strong absorbance in near infrared (NIR) region, the resulted porous Prussian blue nanocubes could lead to more than 80% death of Hela cells after being treated with nanocubes of concentration as low as 100 μg mL−1. Compared to the traditional solid Prussian blue nanoparticles, these porous nanocubes can provide extra space for encapsulating anti-cancer drugs in their porous interior. It is anticipated that these porous Prussian blue nanocubes can be applied as an enabling platform to develop the next generation of multifunctional drug carrier for cancer treatments.